UJI EKSPERIMENTAL SEMEN PAPAN PARTIKEL BERBAHAN BAKU LIMBAH FLY ASH BATU APUNG SEBAGAI BAHAN PEREDAM SUARA - Apip Amrullah (ASEAN Journal of Systems Engineering, 2014)
By the development in technology especially in architecture and industry with its noise activity, encourage us to do some efforts to solve noise problem. One might done is utilize pumice as noise absorber. Raw material used in this reaserch is pumice ash. Mixing compotsition variation between cement composition, pumice ash as sand subtitution, with comparison mixing composition at 1 : 6 (1 cemen : 6 ash), 1 : 8 (1 cement : 8 ash :), 1 : 10 (1 cement : 10 ash). Sound absorbtion coefisien are measured by standing wave tube apparatus. The result of the research indicates that mixing composition affects the sound absorbtion coefisien. Reaserch shows taht 1 : 6, 1 :8 and 1 : 10 sound absorbtion coefisien which is 0.96, 0,86 and 0.89 in 8000 Hz frequency. Comparison at 1 : 6, 1 : 8 and 1 : 10 (cement : sand ) has the best absorbtion coefisien at comparation 1 : 10 which is 0.98 with 4000 Hz frequency (middle level frequency).